Fiber laser with built-in FBG and LPFG for simultaneous two parameters sensing. (17th November 2021) - Li, Dong-Chang; Liaw, Shien-Kuei; Chen, Bo-Wei; Lee, Hsin-Che; Yu, Yi-Lin; Kishikawa, Hiroki; Goto, Nobuo
Abstract: This work aims to measure the liquid level and temperature at the same time. We propose a fiber laser based on Bragg grating (FBG) and a long-period fiber grating (LPFG) for simultaneously two-parameter sensing. It has one wavelength peak induced by the FBG and one central dip induced by the LPFG. The resulting temperature varies from 25 °C to 50 °C in 7.5 nm wavelength drifts of LPFG with linearity R 2 of 0.9994. The sensitivity of the FBG liquid level sensing will be affected by the temperature change, ranging from—0.12 nm cm −1 at low temperature to—0.004 nm cm −1 at high temperature, and the linearity R 2 is about 0.9967. Thanks to the laser cavity, the proposed fiber laser with an extensive dynamic range could be used for remote monitoring.